Temperature extremes in the south of South America in relation to Atlantic Ocean surface temperature and Southern Hemisphere circulation - Barrucand, M. (2008)
The objective of this research is to study the main variability modes of the frequency of extreme temperatures in the south of South Amenica, their relation to sea surface temperatures (SSTs), and some indices of atmospheric circulation in the Southern Hemisphere. Observational data and reanalysis data were used for this purpose over the 1964-2003 period. An initial analysis showed that between the months of March and June, the frequency of wann events (especially warm nights) is highly associated with the SST in coastal zones. A wavelet analysis showed that the main variability mode found at a seasonal scale was an 8-year wave signal present in spning that remains active until the 1990s; it was noticeable in the analysis of cold nights, Atlantic SSTs, Pacific SSTs, and the Southern Annular Mode (SAM). A cross-wavelet analysis among them reflected this signal as a common variability mode, with the positive phase of the SAM congruent with the warmest conditions in the coastal zones of the Atlantic Ocean and lower cases with cold nights at the reference meteorological stations analyzed. Although longer series are desirable for low-frequency variability analysis, the results agree with previous studies that take into account an 8-year periodicity of the baroclinic waves at the Southern Hemisphere, supporting the relevance of the 8-year signal. Copyright 2008 by the American Geophysical Union.